2014
DOI: 10.5037/jomr.2014.5206
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Erosion among the Young Regular Swimmers in Kaunas, Lithuania

Abstract: ObjectivesTo determine prevalence of dental erosion among competitive swimmers in Kaunas, the second largest city in Lithuania.Material and MethodsThe study was designed as a cross-sectional survey, with a questionnaire and clinical examination protocols. The participants were 12 - 25 year-old swimmers regularly practicing in the swimming pools of Kaunas. Of the total of 132 participants there were 76 (12 - 17 year-old) and 56 (18 - 25 year-old) individuals; in Groups 1 and 2, respectively. Participants were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 17 publications
2
13
0
11
Order By: Relevance
“…A number of medications may cause dental erosion, mostly vitamin C tablets and iron formulations that are too acidic, especially when in chewable form (6). A lifestyle that emphasizes a "healthy" diet and exercise with regular, continuous use of isotonic drinks could potentially lead to increased dental erosion (4,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of medications may cause dental erosion, mostly vitamin C tablets and iron formulations that are too acidic, especially when in chewable form (6). A lifestyle that emphasizes a "healthy" diet and exercise with regular, continuous use of isotonic drinks could potentially lead to increased dental erosion (4,6).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between oral health and sports has been investigated (2,3): a systematic review reported that athletes had high prevalences of oral diseases, including dental caries (15-75%), moderate-to-severe periodontitis (≤15%), dental erosion (36-85%), and pericoronitis/ impacted third molars (5-39%) (3). Among the oral diseases that affect athletes, dental erosion is defined as progressive, irreversible loss of tooth tissue due to acid dissolution, without bacterial involvement (4). It results when a tooth is in frequent contact with acid (5).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies stated the erosive risk in subjects with pathology inducing GER: a higher risk (3.37) of dental erosion in subjects with frequent vomiting episode [24], erosion increased risk in all dental surfaces (OR = 2.15 for the occlusal surface, 2.84 for the palatal surface and 2.91 for the buccal surface) in individuals with GER [18], and the presence of symptoms associated with GER and to frequent vomiting showed a significant relationship with tooth erosion [25]. However, recent findings from the Margaritis et al study revealed the absence of a significant relationship between the presence of GER and tooth erosion in the population studied [26].…”
Section: Discussionmentioning
confidence: 99%
“…Frente a un pH de 2.4 de las bebidas carbonatadas, se produce una acelerada liberación de iones de calcio y fosfato desde el esmalte hacia el medio circundante (20) , el ambiente bucal si bien es capaz de recuperar su pH neutro natural después de la ingestión de sustancias ácidas, el acelerado y pronunciado descenso no consigue ser cubierto por la saliva, afectando la superficie dental (21) constituyéndose la erosión en un proceso destructivo crónico (22) contrapuesto a la acción ácida producida por bacterias desencadenantes de la caries dental (23) .…”
Section: Discussionunclassified